2018
DOI: 10.3389/fphys.2018.00443
|View full text |Cite
|
Sign up to set email alerts
|

High pH-Sensitive Store-Operated Ca2+ Entry Mediated by Ca2+ Release-Activated Ca2+ Channels in Rat Odontoblasts

Abstract: Odontoblasts play a crucial role in dentin formation and sensory transduction following the application of stimuli to the dentin surface. Various exogenous and endogenous stimuli elicit an increase in the intracellular free calcium concentration ([Ca2+]i) in odontoblasts, which is mediated by Ca2+ release from intracellular Ca2+ stores and/or Ca2+ influx from the extracellular medium. In a previous study, we demonstrated that the depletion of Ca2+ stores in odontoblasts activated store-operated Ca2+ entry (SOC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…Cementoblasts express cation (such as Ca 2+ ) permeable transient receptor potential ankyrin subfamily member 1 (TRPA1) channels, which are known to be sensitive to alkaline extracellular conditions (Tsumura et al, 2013;Kimura et al, 2016) to mediate proliferation and cementum mineralization (Muramatsu et al, 2019). Although confirmation is needed, cementoblast K Ca channel activation may play a particularly important role in cell proliferation and differentiation, and cementum formation, via crosstalk with intracellular Ca 2+ signaling pathways mediated by high pH-sensitive TRP channel subfamily members (Kimura et al, 2018). TRPA1 channels also mediate mechanosensitive Ca 2+ signaling (Sato et al, 2013(Sato et al, , 2018Tsumura et al, 2013;Shibukawa et al, 2015;Kimura et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Cementoblasts express cation (such as Ca 2+ ) permeable transient receptor potential ankyrin subfamily member 1 (TRPA1) channels, which are known to be sensitive to alkaline extracellular conditions (Tsumura et al, 2013;Kimura et al, 2016) to mediate proliferation and cementum mineralization (Muramatsu et al, 2019). Although confirmation is needed, cementoblast K Ca channel activation may play a particularly important role in cell proliferation and differentiation, and cementum formation, via crosstalk with intracellular Ca 2+ signaling pathways mediated by high pH-sensitive TRP channel subfamily members (Kimura et al, 2018). TRPA1 channels also mediate mechanosensitive Ca 2+ signaling (Sato et al, 2013(Sato et al, , 2018Tsumura et al, 2013;Shibukawa et al, 2015;Kimura et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…To induce membrane stretching [3,29], a hypotonic solution (200 mOsm/L) was prepared by decreasing the concentration of mannitol to 64 mM. For the high-pH (pH 8) extracellular solution, 12 mM NaHCO 3 in Krebs solution was changed to 8 mM (pH 8) NaOH [6,7]; this change had no effect on the extracellular free Ca 2+ concentration in the test solution. Caloxin 1b1 was obtained from Karebay Biochem, Inc. (Monmouth Junction, NJ, USA).…”
Section: Solutions and Reagentsmentioning
confidence: 99%
“…Odontoblasts play critical roles in the generation of dentinal sensitivity (known as the odontoblast hydrodynamic receptor model [1]) and dentin formation (dentinogenesis) in both physiological and pathological settings. We previously reported that odontoblasts are sensory receptor cells capable of detecting multiple stimuli applied to the dentin surface [1][2][3][4][5][6][7][8]. These stimuli at the surface are transformed into dentinal fluid movements, which elicit intracellular Ca 2+ signaling by increasing the concentration of intracellular free Ca 2+ ([Ca 2+ ] i ) through Ca 2+ influx activated by mechanosensitive ion channels, transient receptor potential (TRP) channel subtypes, and Piezo1 channels [1,5].…”
Section: Introductionmentioning
confidence: 99%
“…In odontoblasts Ca 2+ signaling and Ca 2+ transport mechanism are involved in sensory transduction upon exposure of dentin to diverse stimuli and in dentin mineralization [81][82][83][84][85][86][87][88][89][90]. It has been shown that odontoblasts express Orai1 [45,91] as well as Stim1 and Stim2 [49] and that SOCE is activated upon intracellular Ca 2+ store depletion in odontoblasts [85,90]. Ca 2+ influx into odontoblasts is also mediated by voltage-gated L-type channels [81,83,92] and odontoblasts express L-type Ca v 1.2 channels [93].…”
Section: Probable Roles For Homer Proteins During Tooth Formationmentioning
confidence: 99%